ChemInform Abstract: Electronic Transport Properties of Transition Metal Dichalcogenide Field‐Effect Devices: Surface and Interface Effects. Issue 50 (December 2015) - Schmidt, Hennrik; Giustiniano, Francesco; Eda, Goki
Abstract: Review: 212 refs.